Virulent Bacteria as Inflammatory and Immune Co-Factor in Colon Carcinogenesis: Evidence From Two Monozygotic Patients and Validation in CRC Patient and Healthy Cohorts - Sobhani, Iradj; Bergsten, Emma; Charpy, Cecile; Chamaillard, Mathias; Mestivier, Denis (Frontiers in Cellular and Infection Microbiology, 2021)
Colorectal carcinoma (CRC) is a common disease, the incidence of which is increasing according to Western lifestyle; it remains to have a poor prognosis. Western nutriments are presumed to induce mild inflammation within the colonic mucosa, resulting in the accumulation of DNA alterations in colonocytes through a multistage carcinogenesis process. This suggests that most CRCs are related to the environment. Of interest, fecal microbiota composition has been shown yielding a novel approach regarding how environment changes may impact health and disease. Here, we compare whole shotgun metagenomic gut microbiota of two monozygotic twin sisters, one of whom is suffering from an advance colorectal tumor with a profound disequilibrium of the composition of the gut microbiota due to the overexpression of virulent bacteria such as E. coli, Shigella, and Clostridium species in the colon cancer patient’s feces contrasting with low levels of bacterial species such as Faecalibacterium and Akkermansia usually enriched in the healthy adults’ microbial flora. The disequilibrium in microbiota of the CRC patient’s feces as compared to her monozygotic twin sister is linked to inflammatory and immune cell infiltrates in the patient’s colonic tissue. We speculate on the role of microbiota disequilibrium on the immune-tolerant cell infiltrate within CRCs.